2018
DOI: 10.5500/wjt.v8.i3.61
|View full text |Cite
|
Sign up to set email alerts
|

Utility of central venous pressure measurement in renal transplantation: Is it evidence based?

Abstract: Adequate intravenous fluid therapy is essential in renal transplant recipients to ensure a good allograft perfusion. Central venous pressure (CVP) has been considered the cornerstone to guide the fluid therapy for decades; it was the only available simple tool worldwide. However, the revolutionary advances in assessing the dynamic preload variables together with the availability of new equipment to precisely measure the effect of intravenous fluids on the cardiac output had created a question mark on the futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…The high target CVP advocated in literature was abandoned, aiming for less liberal fluid administration. This accords with many reports questioning the use of CVP as a reliable monitor of fluid status in adults . Based upon our experience with advanced hemodynamic monitoring in children, we chose the transpulmonary thermodilution (TPTD) technique to measure CO as this technique has been validated and is designated as the gold standard in children …”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…The high target CVP advocated in literature was abandoned, aiming for less liberal fluid administration. This accords with many reports questioning the use of CVP as a reliable monitor of fluid status in adults . Based upon our experience with advanced hemodynamic monitoring in children, we chose the transpulmonary thermodilution (TPTD) technique to measure CO as this technique has been validated and is designated as the gold standard in children …”
Section: Introductionmentioning
confidence: 78%
“…TA B L E 3 Values of hemodynamic variables obtained at three different time points: pre-transplantation (t0), post-reperfusion (t1) and in the intensive care unit, without hemodynamic support (t2) (n = 12) (2) , .008 (3) , .002 (4) , .154 (5) , .472 (6) , <.0001 (7) , >.999 (8) , .003 (9) , .001 (10) , .007 (11) and .0007 (12) . c CVP was obtained in 10 patients at 2 times points; the difference between values for CVP was not statistically significant (Student's t-test for paired data: P = .76).…”
Section: Hemodynamic Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors include operating table position, which is not always flat and the surgeon may left or right tilt it to have more access to the iliac vessels, the pressure effect of surgical retractors on the abdominal viscera and venous return, and the positive pressure ventilation during the procedure that can also affect venous return. [ 20 ] Systematic reviews revealed a weak correlation between CVP and blood volume, as well as CVP's inability to predict hemodynamic responses to a fluid challenge. [ 21 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 13 ] This invented newer dynamic indices based GDFT to accurately assess fluid responsiveness. [ 14 15 ] These newer techniques along with adequate haemodynamic optimisation in various high-risk surgeries including transplantation had improved the early recovery and significantly reduced the postoperative complications. [ 16 17 ] In renal transplant recipients, even CFT (TED) guided fluid therapy had proven better outcomes to CVP with lesser side effects.…”
Section: Discussionmentioning
confidence: 99%